Factors that influence on employee engagement at Urban Transformation Centre (UTC) Melaka / Nuraqilah Zainal - Zainal, Nuraqilah (Faculty of Business and Management, 2018)
The study explored the factors influence on employee engagement at Urban Transformation Centre (UTC) Melaka. The purpose of this study is to investigate whether the employee loyalty influence employee engagement and to examine how leadership can effect employee engagement. This empirical study collected quantitative data from employee at Urban Transformation Centre (UTC) Melaka, 140 questionnaire were distributed and 123 were obtained. Two variables are measure which are employee loyalty, and leadership. Two dimensions of loyalty are namely, affective commitment and continuous commitment. The findings show that significant relationships between affective commitment and employee engagement, and significant relationships between leadership and employee engagement. While, no significant relationship between continuous commitment and employee engagement. The findings of this study are limited to Urban Transformation Centre (UTC) Melaka. There are recommendations to the employer, leader and for future research to be conducted for better understanding in future.